Does a Picture Paint a Thousand Words? Evidence from a Microcredit Marketing Experiment - Giné, Xavier (World Bank, Washington, DC, 2012)
Female entrepreneurship is low in many developing economies partly because of constraints on women's time and mobility, which are often reinforced by social norms. This paper analyzes a marketing experiment designed to encourage women to adopt a new microcredit product. A brochure with the same content but two different covers was randomly distributed among male and female borrowing groups. One cover featured five businesses run by men, while the other showed identical businesses run by women. Men and women responded to psychological cues. Among men who were not business owners, had lower measured ability and whose wives were less educated, the responses to the female brochure were more negative, as did female business owners with low autonomy within the household. Women with relatively high levels of autonomy had a similar negative response to the male brochure, while there was no effect on female business owners with autonomy. Overall, these results suggest that women's response to psychological cues, such as positive role models, may be affected by their level of autonomy at home, and more intensive interventions may be required for more disadvantaged women.